2015
DOI: 10.1371/journal.pgen.1004923
|View full text |Cite
|
Sign up to set email alerts
|

ASAR15, A cis-Acting Locus that Controls Chromosome-Wide Replication Timing and Stability of Human Chromosome 15

Abstract: DNA replication initiates at multiple sites along each mammalian chromosome at different times during each S phase, following a temporal replication program. We have used a Cre/loxP-based strategy to identify cis-acting elements that control this replication-timing program on individual human chromosomes. In this report, we show that rearrangements at a complex locus at chromosome 15q24.3 result in delayed replication and structural instability of human chromosome 15. Characterization of this locus identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
139
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(143 citation statements)
references
References 57 publications
(134 reference statements)
4
139
0
Order By: Relevance
“…However, very few loci in mammalian genomes display asynchronous replication, and so far all of them have been linked to either X Chromosome inactivation in female cells or to parental imprinting/monoallelic gene expression (Reik and Walter 2001;Goldmit and Bergman 2004;Gimelbrant et al 2007;Farkash-Amar et al 2008;Stoffregen et al 2011;DeVeale et al 2012;Koren et al 2014;Mukhopadhyay et al 2014;Donley et al 2015). Moreover, direct comparison of known asynchronously replicated or monoallelically expressed genes to our categories of genes revealed that such genes are mostly constitutively replicated (Supplemental Fig.…”
Section: C-class Gene Transcription Is Frequently Coordinated With Rtmentioning
confidence: 90%
“…However, very few loci in mammalian genomes display asynchronous replication, and so far all of them have been linked to either X Chromosome inactivation in female cells or to parental imprinting/monoallelic gene expression (Reik and Walter 2001;Goldmit and Bergman 2004;Gimelbrant et al 2007;Farkash-Amar et al 2008;Stoffregen et al 2011;DeVeale et al 2012;Koren et al 2014;Mukhopadhyay et al 2014;Donley et al 2015). Moreover, direct comparison of known asynchronously replicated or monoallelically expressed genes to our categories of genes revealed that such genes are mostly constitutively replicated (Supplemental Fig.…”
Section: C-class Gene Transcription Is Frequently Coordinated With Rtmentioning
confidence: 90%
“…In general, homologues replicate highly synchronously with very few regions showing allelic differences in RT or in origin usage related to DNA sequence variation, although some reach statistical or disease-associated significance worth further investigation [24*,66*,67,68*,69*]. An elegant series of recent papers has revealed a new class of cis -acting elements involved in the regulation of RT, mitotic condensation and chromosome stability [7072**]. These elements consist of monoallelically expressed long non-coding RNAs that appear to be present on each mammalian chromosome, and interact in cis to regulate RT, monoallelic gene expression and structural stability of the entire chromosome [72**].…”
Section: Intrinsic and Extrinsic Variation In Rt And Large-scale Chromentioning
confidence: 99%
“…An elegant series of recent papers has revealed a new class of cis -acting elements involved in the regulation of RT, mitotic condensation and chromosome stability [7072**]. These elements consist of monoallelically expressed long non-coding RNAs that appear to be present on each mammalian chromosome, and interact in cis to regulate RT, monoallelic gene expression and structural stability of the entire chromosome [72**]. Overall, these results uncover specific mechanisms that control intrinsic allelic variation in RT that are certain to be the subject of much investigation in the coming years.…”
Section: Intrinsic and Extrinsic Variation In Rt And Large-scale Chromentioning
confidence: 99%
“…Another particularly promising prospect for an RNA that likely spreads across Chromosome 15 is ASAR15 (Figure 3E), discovered because disruption of this large locus impacts the replication timing and stability of the chromosome [30]. Several published images show an extensive overlap of ASAR15 RNA with chromosome 15 DNA (marked by many loci rather than a DNA library).…”
Section: A Few New Prospective “Chromosomal” Rnas: the Challenge Is Tmentioning
confidence: 99%
“…D) An illustration of the amount of interphase X-chromosome territory typically “painted” by XIST RNA (green) and XACT RNA (yellow) in a pluripotent cell (as seen by us and in published images) [28]. E) An illustration of the amount of interphase chromosome-15 territory typically “painted” by ASAR5 RNA (as seen in published images) [30]. F) An illustration of the amount of a human interphase chromosome territory typically “painted” by Cot-1 ecRNA in mouse/human hybrid cells (as seen in our published images) [39].…”
Section: Figurementioning
confidence: 99%